Comparative Analysis of Grammatical Difficulties in TOEFL SWE Section Across Disciplinary Backgrounds: A Mixed-Methods Study of Indonesian EFL Learners - Danuwijaya, Ari Arifin; Nawas, Abu (JOLLT Journal of Languages and Language Teaching, 2025)
Grammatical competence remains fundamental to English proficiency assessment, particularly in standardized tests such as the TOEFL ITP. The Structure and Written Expressions (SWE) section consistently challenges EFL learners, yet research has predominantly focused on English language majors, with limited comparative examination of how academic disciplinary background influences grammatical performance and learner perceptions. This mixed-methods study addressed this gap by investigating grammatical difficulties across three academic programs: Tourism Education, Japanese Language Education, and English Language Education. The study examined 163 Indonesian undergraduate students' performance on the TOEFL ITP SWE section and explored their self-perceived competence and test-related challenges. Quantitative data from a 40-item TOEFL SWE test were analyzed using Classical Test Theory and jMetrik software to calculate item difficulty indices. Qualitative data were collected through self-rating questionnaires and focus group discussions with 15 participants. Results revealed systematic performance differences across disciplines, with Tourism and Japanese Language students demonstrating significantly higher error rates than English majors. Six grammatical constructions consistently emerged as problematic: relative adverbs, causal expressions, inverted sentence structures, word forms, parallel structures, and redundancy. Qualitative analysis identified shared challenges including vocabulary limitations, test format unfamiliarity, and time management difficulties. Notably, English students, despite higher performance, showed unexpected weaknesses in error analysis. The findings demonstrate that grammatical performance in standardized contexts results from complex interactions between linguistic competence, test literacy, and academic background.